Overexpression of catalase prevents hypertension and tubulointerstitial fibrosis and normalization of renal angiotensin-converting enzyme-2 expression in Akita mice - Shi, Yixuan (American Physiological Society, 2013)
We investigated the relationship among oxidative stress, hypertension, renal injury, and angiotensin-converting enzyme-2 (ACE2) expression in type 1 diabetic Akita mice. Blood glucose, blood pressure, and albuminuria were monitored for up to 5 mo in adult male Akita and Akita catalase (Cat) transgenic (Tg) mice specifically overexpressing Cat, a key antioxidant enzyme in their renal proximal tubular cells (RPTCs). Same-age non-Akita littermates and Cat-Tg mice served as controls. In separate studies, adult male Akita mice (14 wk) were treated with ANG 1–7 (500 μg·kg(−1)·day(−1) sc) ± A-779, an antagonist of the Mas receptor (10 mg·kg(−1)·day(−1) sc), and euthanized at the age of 18 wk. The left kidneys were processed for histology and apoptosis studies. Renal proximal tubules were isolated from the right kidneys to assess protein and gene expression. Urinary angiotensinogen (AGT), angiotensin II (ANG II), and ANG 1–7 were quantified by specific ELISAs. Overexpression of Cat attenuated renal oxidative stress; prevented hypertension; normalized RPTC ACE2 expression and urinary ANG 1–7 levels (both were low in Akita mice); ameliorated glomerular filtration rate, albuminuria, kidney hypertrophy, tubulointerstitial fibrosis, and tubular apoptosis; and suppressed profibrotic and proapoptotic gene expression in RPTCs of Akita Cat-Tg mice compared with Akita mice. Furthermore, daily administration of ANG 1–7 normalized systemic hypertension in Akita mice, which was reversed by A-779. These data demonstrate that Cat overexpression prevents hypertension and progression of nephropathy and highlight the importance of intrarenal oxidative stress and ACE2 expression contributing to hypertension and renal injury in diabetes.